Produções correntes em arquitectura: a porta para uma diferente gramática do projecto do início do século XX - Rui Jorge Garcia Ramos (2005)
The bourgeois mansions, produced by architects with classical and romantic tendencies by the 19th century European schools, are simultaneous to other rational and systematised production. The same offices took into account a new concern on the bourgeois social space, abiding to the shape of private life of the dwelling space under a controlled investment.